DETERMINAN PENENTUAN FEE AUDIT EKSTERNAL DALAM KONVERGENSI IFRS - Sukron Dawami; Julian Maradina (Universitas Pamulang, 2017)
This study aims to examine the determinants of external audit fees in IFRS convergence. There are several factors that are expected to affect audit fees such as firm size, profitability level and KAP type. These factors are expected to increase external audit fees. In addition, this study also linked the application of IFRS and auditing areas that are still few in Indonesia. This study is a modification of Ulfasari research (2014). This study adds independent variables and uses secondary data from manufacturing companies listed on the BEI 2010-2014. This research use purposive sampling method and get sample as many as 130 companies. Thereafter, firm size, profitability level, KAP type and audit fee were tested using multiple linear regression analysis found in SPSS version 21. Before the regression test, the data were first tested using the classical assumption test. The result of the research shows that firm size has significant effect to audit fee, profitability level has significant effect to audit fee. While KAP type has no significant effect on audit fee. Simultaneously firm size, profitability level and KAP type have effect on audit fees in IFRS convergence.